The response of income inequality to positive oil rents shocks in Iran: Implications for the post-sanction period - Mohammad Reza Farzanegan; Tim Krieger (Philipps-University Marburg, School of Business and Economics, 2017)
We study the short and long run responses of income inequality to the positive oil and gas rents per capita shocks in Iran from 1973 to 2012. Using vector autoregression (VAR)-based impulse response functions, we find a positive and statistically significant response of income inequality to oil rents booms within 4 years after the shock. The Autoregressive-Distributed Lag (ARDL) results show that a 10 percent increase in oil and gas rents per capita leads to 1.1 percent increase in income inequality in the long run. The results are robust after controlling for income-distribution channels in Iran. Our analysis can help policy makers to evaluate and accommodate the possible positive or negative effects of lifting sanctions on inequalities in Iran.
Keywords: Q33; Q38; D63; 330; oil rents; inequality; VAR; ARDL; sanctions; Iran